Effect of Dispersing In Situ Al-Cu Intermetallic Compounds on Joint Strength in Friction Stir Welding of AA3003-H18 Sheets - Behrouz Abnar; Mousa Javidani (Metals, 2024)
In this study, friction stir welding (FSW) was employed to join AA3003-H18 sheets by incorporating in situ Al-Cu intermetallic compounds within the stir zone. The FSW process was carried out under three distinct conditions: (I) without applying powder, (II) by introducing Cu powder, and (III) by incorporating Cu-Al mixed powder (50 vol.% Cu, 50 vol.% Al). The powder was embedded into the gap between two sheets. Subsequently, two-pass FSW, involving both forward and backward movements, was conducted with a rotational speed of 1200 rpm and traverse speed of 100 mm/min across all three experimental conditions. In the second and third conditions, the formation of in situ intermetallic compounds occurred through a solid-state reaction between Cu particles and Al within the stir zone. Examination of the stir zone through optical and electron microscopic studies revealed that the utilization of Cu-Al mixed powder resulted in finer and more uniformly distributed Cu clusters and Al-Cu intermetallics than samples welded with Cu powder alone. Notably, the stir zone of samples incorporating Cu-Al mixed powder exhibited finely dispersed, completely gray Al-Cu intermetallic particles, whereas those with only Cu powder displayed predominantly coarse core-shell particles in the microstructure. The introduction of Cu-Al mixed powder during FSW resulted in a stir zone with an average hardness of 74 HB, showing a 14% increase compared to the cases where Cu powder alone was added (65 HB). Tensile tests, conducted in both transverse and longitudinal directions on the FSWed samples, did not exhibit a consistent trend across the three mentioned conditions. Transverse tensile strength consistently ranged between 107 and 110 MPa, with joint efficiency varying from 52% to 54%. However, the longitudinal tensile strength of the joint with added Cu-Al mixed powder (158 MPa) surpassed those welded with Cu powder alone (134 MPa).